Lubrication performance of an ammonium cation-based ionic liquid used as an additive in a polar oil. (December 2017) - Viesca, J.L.; Mallada, M.T.; Blanco, D.; Fernández-González, A.; Espina-Casado, J.; González, R.; Hernández Battez, A.
Abstract: This paper studies the tribological behavior of the ionic liquid methyltrioctylammonium bis(trifluoromethylsulfonyl)imide ([N1888 ][NTf2 ]) as additive at different concentrations (1.25, 2.50, 3.75 and 5.00 wt%) in a polar base oil (diester). A tribometer using a ball-on-disk reciprocating configuration under fully flooded lubrication was used at a frequency of 15 Hz, at three different loads (40, 80 and 120 N), stroke length of 4 mm, and duration of 45 min. Worn surface on the disk was studied by confocal microscopy, SEM and XPS. Main results showed similar coefficient of friction for all lubricant samples; but different wear results were found at different loads, probably related with the chemical states found for fluorine on the worn surface and the temperature-dependent adsorption-desorption processes. Highlights: [N1888 ][NTf2 ] as additive in polar oil competes with base oil for surface interaction. [N1888 ][NTf2 ] as additive in a polar oil hardly change friction. [N1888 ][NTf2 ] showed wear reduction properties as additive in a polar oil. Tribology results are related with the IL-surface chemical interaction.